Reproductive Health Knowledge and Care Seeking Behavior of Bangladeshi School Going Adolescent Girls: A Qualitative Study in A Demajani Village Area of Bogura District - Rashid, Sarawat; Rahman, Md. Siddiqur; Mahejabin, Andalib; Abedin, Maupiya (Advances in Social Sciences Research Journal, 2023)
The cultural context in Bangladesh generally discourages adolescent from giving opinions, speaking up or questioning adults. So, their needs and vulnerabilities are often unaddressed and adolescent friendly services still unfamiliar concepts. In such cultural context, adolescent girls’ reproductive knowledge and healthcare seeking behaviour is important. Improper and delay in seeking care may also result in increased risk in the community. Understanding the pattern of healthcare-seeking behaviour could help public health practitioners and policy makers to improve the healthcare system and health promotion strategies. The objectives of the study were to unveil the adolescents’ girl knowledge on reproductive health. To elicit the types of care adolescent girl sought when they get ill and to identify determinates of the adolescent girl for seeking care. Focused group discussion and in-depth interview was conducted with adolescent unmarried school going girls at Demajani village under Bogura District in January 2023. The study followed by the health belief model. Respondents were going through the mental and physical changes as they were in adolescent stage. They leant about the reproductive health from their female family members. They share their physical problems with the peer group and tried to solve it by home remedies and then to the qualified doctor. Choice of treatment was dependent on their perceived susceptibility and severity. Respondents were depended on parent as they are unmarried. Their family was motivated by the communities. Therefore, their treatment seeking actives sometimes ignored the availability, affordability, and accessibility of the health services.